Discovery of High Abundances of Aster-Like Nanoparticles in Pelagic Environments: Characterization and Dynamics - Colombet, Jonathan; Billard, Hermine; Viguès, Bernard; Balor, Stéphanie; Boulé, Christelle; Geay, Lucie; Benzerara, Karim; Menguy, Nicolas; Ilango, Guy; Fuster, Maxime; Enault, François; Bardot, Corinne; et al. (Frontiers in Microbiology, 2019)
This study reports the discovery of Aster-Like Nanoparticles (ALNs) in pelagic environments. ALNs are pleomorphic, with three dominant morphotypes which do not fit into any previously defined environmental entities (i.e. ultramicro-prokaryotes, controversed nanobes, and non-living particles (biomimetic mineralo-organic particles, natural nanoparticles or viruses)) of similar size. Elemental composition and selected-area electron diffraction patterns suggested that the organic nature of ALNs may prevail over the possibility of crystal structures. Likewise, recorded changes in ALN numbers in the absence of cells are at odds with an affiliation to until now described viral particles. ALN abundances showed marked seasonal dynamics in the lakewater, with maximal values (up to 9.0±0.5 x 107 particles·mL-1) reaching eight times those obtained for prokaryotes, and representing up to about 40% of the abundances of virus-like particles. We conclude that (i) aquatic ecosystems are reservoirs of novel, abundant and dynamic aster-like nanoparticles, (ii) not all virus-like particles observed in aquatic systems are necessarily viruses, and (iii) there may be several types of other ultra-small particles in natural waters that are currently unknown but potentially ecologically important.